INTRUSIVE-MAGMATIC COMPLEXES OF WILHELM ARCHIPELAGO, WEST ANTARCTICA (PART 1 – INTRUSIONS OF GABBROIDS, DIORITES AND GRANITOIDS) - Аleksieienko, А.; Marushchenko, О.; Митрохин, О.; Бахмутов, В.; Алексєєнко, А.; Митрохина, Т.; Марущенко, О. (Київський національний університет імені Тараса Шевченка, 2021)
The Wilhelm Archipelago and the adjacent coast of Graham Land are typical areas of calc-alkaline magmatism associated with the protracted evolution of the Antarctic Peninsula igneous belt. The authors studied intrusive complexes of the Wilhelm Archipelago (WA) in order to characterize their geographical distribution, geological occurrence and age, mineralogical and petrographical features. Geological surveys revealed that gabbro, diorite, and granitoid intrusions are widespread on the WA. Due to the processes of tectonic uplift and exhumation, both apical and bottom parts of individual intrusive bodies can be exposed on the modern erosion level. Recent geological observations have shown that plutons of different ages intersect each other in a complex sequence. This made it possible to determine their relative geological age and reconstruct the general direction of the deep magmatic development from the Early Cretaceous to the Early Paleogene, inclusive. It has been proved that the oldest massifs of gabbroids are parts of much larger intrusive bodies. They were formed in the period between the Jurassic and the Early Cretaceous periods. Crystallization differentiation of basaltic magmas gave them various scale layering. In the bottom parts of gabroid intrusions there were conditions for the formation of Fe-Ti-V and Cu-Ni-EPG mineralization. Diorite and granitoid intrusions occupy much larger areas compared to gabbroids. The formation of diorite intrusions took place in the period between the Early Cretaceous and the Paleocene. Although the oldest gabbroids were formed much earlier than diorites, the phenomena of magmatic mingling in the latter indicate that magmas of basic and intermediate composition could also synchronously intrude in common magmatic chambers. Granitoid magmatism on the WA covers the Late Cretaceous and the Paleogene periods. Most granitoid intrusions formed in the Paleocene after the main phase of tectonic deformations. Cu-Mo mineralization may be associated with these intrusions.

Архіпелаг Вільгельма та прилегле узбережжя Землі Греяма є типовими районами розвитку вапняно-лужного магматизму, пов'язаного з тривалою еволюцією магматичного поясу Антарктичного півострова. Автори дослідили інтрузивномагматичні утворення архіпелагу Вільгельма (АВ) з метою охарактеризувати їх географічну поширеність, умови залягання, геологічний вік та мінералого-петрографічні особливості. У результаті виконаної геологічної зйомки з'ясовано, що на АВ поширені інтрузиви габроїдів, діоритів та гранітоїдів. Завдяки процесам тектонічного підняття та ексгумації на одному рівні сучасного ерозійного зрізу можуть відслонюватися як апікальні, так і придонні частини окремих інтрузивних тіл. Новітні геологічні дослідження вказують на те, що різновікові плутони перетинають один одного у складній послідовності. Це дало можливість визначати їх відносний геологічний вік та реконструювати загальну спрямованість розвитку глибинного магматизму від ранньої крейди до раннього палеогену включно. Доведено, що найдавніші масиви габроїдів є частинами значно більших інтрузивних тіл. Вони сформувалися у часовому проміжку між юрським та ранньокрейдяним періодами. Кристалізаційна диференціація базитових магм надала їм розшарованості різного масштабу. У донних частинах габроїдних інтрузивів існували умови для формування Fe-Ti-V та Cu-Ni-EPG зруденіння. Діоритові та гранітоїдні інтрузиви займають на АВ набагато більші площі порівняно з габроїдами. Формування діоритових інтрузивів відбулося у часовому проміжку між ранньою крейдою та раннім палеогеном. Хоча найдавніші габроїди утворилися значно раніше діоритів, явища магматичного змішування в останніх вказують на те, що магми базитового та середнього складу могли й синхронно інтрудувати у спільні магматичні камери. Гранітоїдний магматизм АВ охоплює пізньокрейдяний та палеогеновий періоди. Більшість гранітоїдних інтрузивів АВ сформувалася у палеоцені після головної фази орогенічних деформацій. Саме із цими інтрузивами може бути пов'язана Cu-Mo мінералізація.
ІНТРУЗИВНО-МАГМАТИЧНІ УТВОРЕННЯ АРХІПЕЛАГУ ВІЛЬГЕЛЬМА ЗАХІДНОЇ АНТАРКТИКИ (ЧАСТИНА 1 – ІНТРУЗИВИ ГАБРОЇДІВ, ДІОРИТІВ ТА ГРАНІТОЇДІВ)
Keywords: геологія; вапняно-лужний магматизм; Антарктичний півострів; geology; calc-alkaline magmatism; Antarctic Peninsula